(untitled) (LACCEI, 2024)
The aim of this study was to investigate the impact of educational factors on students’ psychological factors, including locus of control and need for achievement, as well as their soft skills self-perception. A regression analysis was conducted for each independent variable, and the results showed that none of the tested formative factors significantly affected locus of control. However, the type of sport students practiced and their residence during university had a significant effect on their need for achievement. Additionally, certain educational factors, such as the type of school attended before college, as well as the student’s residence during high school and university, and the type of sport practiced, had a significant impact on students’ self-assessment of their soft skills. These findings suggest that understanding the impact of educational factors on students’ need for achievement and soft skills could help promote entrepreneurship among students from different educational backgrounds.